Nuevos registros fungicos en leguminosas de la estacion de pastos y forrajes de Niña Bonita - Estrada, G.=700 1 Lopez, D.; Lopez, M.O.
(Es, En)
Ilus., 13 ref.
Keywords: HONGOS FITOPATOGENOS; PASTIZALES; HOSPEDEROS; CUBA